Snow cornice dynamics as a control on plateau edge erosion in central Svalbard. Issue 5 (19th July 2012) - Eckerstorfer, Markus; Christiansen, Hanne H.; Vogel, Stephan; Rubensdotter, Lena
ABSTRACT Snow cornices grow extensively on leeward edges of plateau mountains in central Svalbard. A dominant wind direction, a snowdrift source area and a sharp slope transition largely control the formation of snow cornices in a barren peri‐glacial landscape. Seasonal snow cornice dynamics control bedrock weathering and erosion in sedimentary bedrock on the Gruvefjellet plateau edge in the valley Longyeardalen. Air, snow and ground temperature sensors, as well as automatic time‐lapse cameras on a leeward facing plateau edge were used to study seasonal cornice dynamics. These techniques allowed for monitoring of cornice accretion, deformation and collapse/melting in great detail. The active layer of the top plateau edge is characterized by high moisture content due to rain before freeze‐up in autumn and cornice meltdown during spring thaw. Thus frost weathering there can be very efficient in this otherwise cold and dry environment. Within the first autumn snowstorms, a vertical fully developed cornice was in place (190 cm thick). The backwall surface beneath the thickest part of the cornice remained in the ice segregation 'frost cracking window' for almost nine months. Highly weathered rock material from the plateau edge is thus incorporated into the cornice during cornice accretion. Brittle snow deformation leads to the opening of cornice tension cracks between the cornice mass and the snowpack on the plateau. These cracks are a prerequisite for cornice collapses, and often trigger cornice fall avalanches on the slope beneath. In these open cornice tension cracks, weathered rock debris, plucked from the plateau edge, can be visible, demonstrating the erosional property of the cornices. The cornice will either collapse or melt, resulting in suspended sediment transport downslope by cornice fall avalanche or release as rock fall respectively. Therefore, cornices both promote and trigger high weathering rates on Gruvefjellet, and thus control presently the development of the rockwall free faces and the talus cones. Copyright © 2012 John Wiley & Sons, Ltd.